1989
DOI: 10.1007/bf00116393
|View full text |Cite
|
Sign up to set email alerts
|

Health and functional status of the elderly in a Polynesian population

Abstract: A health survey was conducted on a random sample of the elderly living on Niue Island in the Southwest Pacific, an island experiencing both the demographic and epidemiological transitions predicted to become common throughout the Third World in the next decades. One-quarter of the respondents reported having no medical impairments and one-third experience no diminution in functional capacity. Visual and auditory losses were common as were respiratory conditions and chronic degenerative disorders. Mobility was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The appropriateness of some existing instruments of functional ability assessment to non-Western cultures may be questionable. In our own study of elderly people in Bombay slums we found, as have others, that an elderly person's cultural environment may not encourage or expect a certain behaviour (covered in an ADL or IADL question, or physical performance test), according to norms of social and economic status, age, sex and prestige (Syryani et al 1988;Barker, 1989). Existing instruments for IADL are especially problematic, and often gender-specific.…”
Section: F U N C T I O N a L A B I L I T Y And N U T R I T I O N A L mentioning
confidence: 55%
See 1 more Smart Citation
“…The appropriateness of some existing instruments of functional ability assessment to non-Western cultures may be questionable. In our own study of elderly people in Bombay slums we found, as have others, that an elderly person's cultural environment may not encourage or expect a certain behaviour (covered in an ADL or IADL question, or physical performance test), according to norms of social and economic status, age, sex and prestige (Syryani et al 1988;Barker, 1989). Existing instruments for IADL are especially problematic, and often gender-specific.…”
Section: F U N C T I O N a L A B I L I T Y And N U T R I T I O N A L mentioning
confidence: 55%
“…Many ADL tasks are performed in quite different ways in non-Western cultures (Jitapunkul et al 1994). Barker (1989) remarked especially on the problem of such populations simply being unused to answering direct probing questions about their lives. Conducting physical performance tests of functional ability in our Bombay slums study we found adaptations were necessary due to constraints of space, light and locally-available equipment.…”
Section: F U N C T I O N a L A B I L I T Y And N U T R I T I O N A L mentioning
confidence: 99%